2016
DOI: 10.3390/horticulturae2040018
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Income Effects of Public GAP Standards: Evidence from the Horticultural Sector in Thailand

Abstract: To reduce potential food hazards and increase the image of Thai horticultural products abroad, the Thai government introduced public standards of Good Agricultural Practices (Q-GAP). What makes orchid and mango producers in Thailand adopt Q-GAP standards and how do these affect their income and export shares? Primary data from 400 certified and non-certified orchid and mango producers was collected from main exporting provinces in Thailand. The binary probit model estimations show that it is the orchid and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Our finding is consistent with Takahiro, Tuan, and Beebout (), who found that net farm income of GAP farmers was higher than that of farmers practicing farming without GAP. Our finding is also consistent with Krause et al (), who found that adoption of public GAP standards resulted in higher income for mango farmers in Thailand.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding is consistent with Takahiro, Tuan, and Beebout (), who found that net farm income of GAP farmers was higher than that of farmers practicing farming without GAP. Our finding is also consistent with Krause et al (), who found that adoption of public GAP standards resulted in higher income for mango farmers in Thailand.…”
Section: Resultssupporting
confidence: 93%
“…Small‐scale farmers in developing countries may benefit more from the adoption of GAP because it could give access to better and bigger markets, both domestically and internationally (Handschuch et al, ). For instance, Krause, Lippe, and Grote () in their study found that mango farmers who adopted public GAP (Q‐GAP) in Thailand earned significantly higher income than their counterparts. In Malaysia, Islam, Arshad, Radam, and Alias () found that tomato‐exporting farmers, under the Malaysian farm certification scheme for GAP (SLAM), almost doubled their productivity and income compared with nonpracticing SLAM farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they could establish the facilities needed to meet GlobalGAP requirements. According to Krause et al (2016) , farm income is one of the motivation factors that increase farmers’ compliance with sustainability standards and good agricultural practices. Farmers with a high yield showed a tendency to consider awareness and information barriers more important than farmers with lower production.…”
Section: Discussionmentioning
confidence: 99%
“…Research into farmers' adoption of public and private GAP programmes has been undertaken in both Vietnam (Loan et al , 2016; Vu Thi et al , 2016) and other developing countries (Krause et al , 2016; Srisopaporn et al , 2015). However, the vast majority of the literature (Lippe and Grote, 2016; Krause et al , 2016; Loan et al , 2016; Vu Thi et al , 2016; Laosutsan et al , 2019) tends to explain farmers' adoption of GAP based on the either some or all of the four following factors:the characteristics of farmers such as age, education level and experience (Kersting and Wollni, 2012; Lippe and Grote, 2016; Krause et al , 2016);the characteristics of farms and households such as farm size, the availability of labour and access to off-farm income (Muriithi et al , 2011; Annor et al , 2016; Loan et al , 2016; Jin and Zhou, 2011);the characteristics of the technology (GAP) such as the complexity of new farming practices, the need for additional labour to implement the new farming practices, the cost of new inputs to meet certification standards and certification costs (Vu Thi et al , 2016; Srisopaporn et al , 2015; Lippe and Grote, 2016); andthe level of support given to farmers under GAP programmes such as technical training, price support or input subsidies (Lippe and Grote, 2016; Kersting and Wollni, 2012; Muriithi et al , 2011). …”
Section: Introductionmentioning
confidence: 99%